Los fundamentos de la diversidad del Sur frente a la intervención militar - Brun, Élodie; Valette, Marie-Françoise (El Colegio de México A.C., 2016)
Analysis of decision taking in countries of the Global South, principally by means of their voting on UN bodies, questions the sovereignist thesis and reveals a double sense of diversity. The poliheuristic approach of foreign policy makes it possible to decipher the complexity of decision making. Beyond a firm commitment to respect for international law, the countries of the Global South appear to be divided, while defending a range of attitudes towards proposed military interventions. Thus some adopt a decision on the basis of their experience, or in line with national or regional political objectives or connected to their relationship with the United States, but also depending on given circumstances and as a response to the evolution of the debate on human rights.